达芬奇机器人治疗肺孤立结节的临床体会 (Zhongguo Fei Ai Za Zhi, 2014)
BACKGROUND AND OBJECTIVE: A solitary pulmonary nodule (SPN) is defined as a round intraparenchimal lung lesion less than 3 cm in size, not associated with atelectasis or adenopathy. The aim of this study is to learn clinical experience of the treatment of SPN with Da Vinci Surgical System. METHODS: A total of 9 patients with solitary pulmonary nodules (SPN) less than 3 cm in diameter was treated with Da Vinci Surgical System (Intuitive Surgical, California) in thoracic surgery department from General Hospital of Shenyang Militrary Region from November 2011 to March 2014. This group of patients included 3 males and 6 females, and the mean age was 51±9.9 yr (range: 41-74 yr). Most of the patients were no obvious clinical symptoms (7 cases were found by physical examination, others were with cough and expectoration). Their median medical history was 12 mo (range: 4 d-3 yr). All the lesions of patients were peripheral pulmonary nodules and the mean diameter of those was (1.4±0.6) cm(range: 0.8-2.8 cm). Wedge-shaped resection or lobectomy was performed depending on the result of rapid pathology and systemic lymph node dissection was done for malignant leision. We used general anesthesis with double lumens trachea cannula. We set the patients in lateral decubitus position with jackknife. The patient cart enter from top of the patient. The position of trocars would be set according to the position of lesion. A 12 mm incision was positioned at the 8th intercostal space in the posterior axillary line as vision port, and two 8 mm incisions were positioned at the 5(th) intercostal space between the anterior axillary line and midclavicular line, and the 8(th) infrascapular line as robotic instrument ports about 10 cm apart from the vision port. One additional auxiliary small incision for instrument without retracting ribs was set at the 7(th) intercostal space in the middle axillary line. RESULTS: There were 4 benign leisions and 5 malignancies identified. Wedge-shaped resection was performed for 4 patients, lobectomy with systemic lymph node dissection for 3 patients (including 2 right middle lobectomies and 1 left upper lobectomy) and wedge-shaped resection with systemic lymph node dissection for 2 patients of poor lung function. All of the 9 cases were completed with total robotic procedure without conversion. The pathological results included 3 inflammatory pseudotumors, 1 hamartoma, 5 adenocarcinomas. All of the 29 patients were hospital discharged smoothly. The patients were followed up for 0.1-18.5 mo (median 11 mo) without recurrence or metastasis. CONCLUSION: The SPN patients should be given active surgical treatments to improve the diagnose rate as well as the cure rate of early non-small cell lung cancer. Since da Vinci Surgical System is a safe and minimally invasive treatment for SPN, it has higher value to the diagnosis and treatment of SPN.